"PROGRAM EMAGREÇA FELIZ”: PROFILE OF PEOPLE PARTICIPATING, A REALITY IN CRICIÚMA (Fiep Bulletin - online, 2014)
Obesity is defined as an excess of fatty tissue in the body. For epidemiological studies has been accepted the concept of obesity by body mass index (BMI) or "Quetelet index," which relates the weight to height to the square, equal to or greater than 30kg/m2 by the World Health Organization (WHO), independent of sex and age. The objective of this study was to verify the profile of people looking for weight loss programs in the city of Criciúma. The sample was composed of 80 individuals aged between 20 and 63 years of both sexes and the larger BMI 30 kg/m². For recruitment of the population of this study was carried out disclosure, with the help of the press sector of the University of the Far South Catarinense, and other media (Internet, newspapers, radio, television, etc.). The volunteers performed: aerobic capacity test (test of miles); Muscle strength (abdominal and bending of arms); Socio-economic profile; Body composition (weight, stature, body mass index (BMI), ratio of circumference of waist and hip, percentage of fat, fat mass in kilograms and lean in Kg). They participate in a program that will include aerobic exercises (walking) and nutritional guidance. When compared with the standards given for all health indices that were evaluated were considered outside the normal or bad. In conclusion, obesity is a disease difficult to treat and high frequency of cardiovascular risk factors even in young patients.
Keywords: Obesity; Profile; Aerobic